2006
DOI: 10.1088/0953-8984/18/3/016
|View full text |Cite
|
Sign up to set email alerts
|

Charge order in photosensitive Bi0.4Ca0.6MnO3films

Abstract: We report the structural and electronic characterization of the charge order phase in Bi0.4Ca0.6MnO3 films, in which photoinduced resistivity changes have been observed at temperatures approaching room temperature. In all films, lattice distortions associated with the charge order are observed, and both the wavevectors and displacements of the distortions are in the plane of the film. Films under compressive and tensile strain are observed to have different resonant xray scattering characteristics-a result tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The photo excitation may induce polarons to break up to generate photo charge carriers to form jump conductance; hence, the photoinduced resistance of YMO/ LSMO heterostructure decreases in macro-scale. 18 In addition, the phase transformations of YMO thin films move to higher temperature under photo excitation. Note that it is totally opposite of the phenomena of photo induced resistance of LSMO thin films, as shown in Figure S2.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The photo excitation may induce polarons to break up to generate photo charge carriers to form jump conductance; hence, the photoinduced resistance of YMO/ LSMO heterostructure decreases in macro-scale. 18 In addition, the phase transformations of YMO thin films move to higher temperature under photo excitation. Note that it is totally opposite of the phenomena of photo induced resistance of LSMO thin films, as shown in Figure S2.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…The variation tendency indicates that YMO thin film has a dominant photosensitivity, in the form of a reduced resistance upon the purple light. The photo excitation may induce polarons to break up to generate photo charge carriers to form jump conductance; hence, the photoinduced resistance of YMO/LSMO heterostructure decreases in macro-scale . In addition, the phase transformations of YMO thin films move to higher temperature under photo excitation.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Experimental work by Deibel and co‐workers on two polymer:fullerene blends revealed a different temperature and density dependence of the bulk carrier mobility and NGR coefficient in two polymer:fullerene blends . The authors proposed that recombination is limited by detrapping of charge from traps in their respective phases, in accordance with earlier theoretical considerations by Nelson . However, in a BHJ with interconnected donor:acceptor phases in the nanometre regime, the domain size needs to be considered in relation to the radius of the CT state in which charges are able to recombine to the ground state.…”
Section: Charge Extraction and Recombinationmentioning
confidence: 64%
“…As temperature decreases, the Bi 0.4 Ca 0.6 MnO 3 thin films undergo a transition to a CO state. 15,19 The onset of the charge ordering is marked by a kink ͑a change in derivative͒ in the temperature dependence of resistivity ͑indicated by arrows in Fig. 2͒.…”
Section: A High Temperature Resistivity Changesmentioning
confidence: 99%
“…15,20 Our x-ray scattering studies on these films showed the presence of superlattice peaks associated with charge ordering below charge-ordering temperatures consistent with the T CO determined from the resistivity measurements. 19 The charge ordering in this material can be partly destroyed by visible light: 15 the resistivity of as-made sample under illumination is considerably smaller than of the sample measured without illumination ͓Fig. 2͑a͔͒.…”
Section: A High Temperature Resistivity Changesmentioning
confidence: 99%